Effectiveness and biological compatibility of different generations of dentin adhesives - Silva, Joao M. F. da [UNESP]; Rodrigues, Jose R. [UNESP]; Camargo, Carlos H. R. [UNESP]; Boas Fernandes, Virgilio Vilas [UNESP]; Hiller, Karl-Anton; Schweikl, Helmut; Schmalz, Gottfried (Springer, 2014)
Besides possessing good mechanical properties, dental materials should present a good biological behavior and should not injure the involved tissues. Bond strength and biocompatibility are both highly significant properties of dentin adhesives. For that matter, these properties of four generations of adhesive systems (Multi-Purpose/Single Bond/SE Plus/Easy Bond) were evaluated.Eighty bovine teeth had their dentin exposed (500- and 200-mu m thickness). Adhesive was applied on the dentin layer of each specimen. Following that, the microshearing test was performed for all samples. A dentin barrier test was used for the cytotoxicity evaluation. Cell cultures (SV3NeoB) were collected from testing materials by means of 200- or 500-mu m-thick dentin slices and placed in a cell culture perfusion chamber. Cell viability was measured 24 h post-exposition by means of a photometrical test (MTT test).The best bonding performance was shown by the single-step adhesive Easy Bond (21 MPa, 200 mu m; 27 MPa, 500 mu m) followed by Single Bond (15.6 MPa, 200 mu m; 23.4 MPa, 500 mu m), SE Plus (18.2 MPa, 200 mu m; 20 MPa, 500 mu m), and Multi-Purpose (15.2 MPa, 200 mu m; 17.9 MPa, 500 mu m). Regarding the cytotoxicity, Multi-Purpose slightly reduced the cell viability to 92 % (200 mu m)/93 % (500 mu m). Single Bond was reasonably cytotoxic, reducing cell viability to 71 % (200 mu m)/64 % (500 mu m). The self-etching adhesive Scotchbond SE decreased cell viability to 85 % (200 mu m)/71 % (500 mu m). Conversely, Easy Bond did not reduce cell viability in this test, regardless of the dentin thickness.Results showed that the one-step system had the best bond strength performance and was the least toxic to pulp cells. In multiple-step systems, a correct bonding technique must be done, and a pulp capping strategy is necessary for achieving good performance in both properties.The study showed a promising system (one-step self-etching), referring to it as a good alternative for specific cases, mainly due to its technical simplicity and good biological responses.
Keywords: Dentin adhesives; Bond strength; Cytotoxicity